Decoding Worker "Reliability": Modern Agrarian Values and Immigrant Labor on New York Dairy Farms. (25th January 2019) - Sexsmith, Kathleen
Abstract: This article examines the reasons offered by New York dairy farmers for hiring undocumented immigrant workers in their milking parlors, and connects those discourses to broader economic and cultural change in U.S. agrarian society. Based on interviews with 25 dairy farmers on 22 farms, this article examines farmers' assessments of the Amish, white non‐Amish, Puerto Rican, and undocumented Latino labor pool. The analysis shows that farmers consider undocumented immigrants the most "reliable" workforce, and that their reliability stems from their deportability and from their separation from their families, which drives them to work long hours. I argue that farmer discourses about immigrant "reliability" must be understood in the context of economic pressure to adopt a more commercial orientation to dairying, and of modern agrarian values that prize urban middle‐class lifestyles. Ultimately, worker "reliability" is a euphemism for the transnational separation of workers from their families, and one that is operationalized by farmers to justify the pursuit of economic success and more leisure time off the farm.